Active wind noise hybrid control in motorcycle helmets - García Violini, Diego Demián (2016)
In this work, three experiments are conducted. In a realistic environment (freeway), a database for the noise dynamics versus velocity in a motorcycle helmet is computed. Next, under the controlled conditions of an anechoic chamber, the models for the feedback (FB) and feedforward (FF) paths in the helmet are obtained by a filtering and identification process. Finally, in the same chamber, a hybrid (FB+FF) robust controller is tested against the actual noise measured in the freeway, and it achieves attenuations between 20 and 30 dB. © 2016, ACOUSTICAL SOCIETY OF JAPAN. All rights reserved.